Low vitamin D status is associated with anaemia in hospitalised cats. (17th February 2020) - Titmarsh, Helen Faye; Woods, Glynn Alan; Cartwright, Jennifer A; Kilpatrick, Scott; Gaylor, Donna; Berry, Jaqueline; Gow, Adam; Bommer, Nick X; Gunn-Moore, Danielle; Handel, Ian; Mellanby, Richard J
Abstract : Background: The major physiological role of vitamin D has traditionally been considered to be the regulation of calcium homeostasis and maintenance of skeletal health. However, there is increasing evidence that vitamin D influences a wider range of physiological processes including erythropoiesis. Vitamin D (25-hydroxyvitamin D, 25(OH)D) deficiency concentrations have been associated with anaemia in human beings. In contrast, the relationship between vitamin D status and erythropoiesis has not been investigated in cats. Methods: Clinical records of cats consecutively presenting between November 2013 and February 2015 were reviewed. For each cat, data including sex, age, breed, serum albumin and creatinine concentrations, and appetite scores were extracted. A multivariable linear regression model was constructed to examine the relationship between 25(OH)D concentrations and these variables. Results: Cats with anaemia had significantly lower 25(OH)D concentrations (median 49.5 nmol/l, n=31) than cats with packed cell volume above the lower limit of the reference range (median 109.0 nmol/l, n=130) (P<0.001). A binary logistic regression found that red blood cell count and mean corpuscular volume were negatively correlated with serum 25(OH)D concentrations (P<0.001 and P=0.007, respectively). Conclusion: Vitamin D (25(OH)D) concentration is positively associated with red blood cell count and mean corpuscular volume in cats with a wide range of different illnesses.